Analysis of physical fitness in students: a comparative study based on social status - Athaya, Haura; Dewantara, Julian; Husein, Muhamad; Taiar, Redha; Shukla, Manish; Malek, Nor Fazila Abd (Universitas Tanjungpura, 2023)
Background and Study Aim. Physical fitness serves as a significant indicator of an individual's health and overall well-being. This research aims to analyze students' physical fitness by conducting a comparative study based on social status. Physical fitness was measured as an indicator of students' health and well-being.Material and Methods. Quantitative descriptive research using survey method. This study involved low-grade students from two elementary schools, namely Mujahidin Elementary School and State Elementary School 16 Rasau Jaya, which have different social status. The sampling method used purposive sampling technique, with a total sample of 40 students from each school. Physical fitness data collection was conducted using the Indonesian Physical Fitness Test. Analysis was assisted using the SPSS 26 application.Results. The results showed a significance value of 0.538 > 0.05 that there was no significant difference in physical fitness between students from both schools based on social status. Although there were variations in the mean physical fitness scores, the differences did not reach the level of statistical significance.Conclusions. This study contributes to the understanding of physical fitness differences based on social status among low-grade students. The implications of the results of this study can be used for the development of more focused intervention programs to improve physical fitness, especially among students with economic and educational challenges.